PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN KAMPAR - Deby Andita; Dedi Afandi; Alida Widiawaty (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTMedical profession in Indonesia has a base on taking their profession responsibility to keep a good relation between doctor and patient named by Kode Etik Kedokteran Indonesia (KODEKI). On Universal Health Coverage Era, doctor as a part of health-care workers is needed to work loyal and professional by implementing KODEKI value. The aim of this study is to discover implementation of KODEKI value on Universal Health Coverage Era in Kampar Regency by assessing six values. This study uses design of exploration method by qualitative approach on three general practitioner in Kampar Regency who were picked by snowball sampling method. Data collection was done by interview and recorded with an audio recorder. The result of this study told that all informans are implementing altruism, responsibility, idealism of profession, accountability for patient, scientific integrity and social integrity on Universal Health Coverage Era could be seen by their statement and daily life as a doctor.Keywords: Kode Etik Kedokteran Indonesia, Universal Health Coverage